Prolonging lifetime for wireless rechargeable sensor networks through sleeping and charging scheduling - Wang, Kun; Wang, Lei; Lin, Chi; Obaidat, Mohammad S.; Alam, Muhammad (International journal of communication systems, 2020)
Summary Prolonging network lifetime is a fundamental requirement in wireless sensor network (WSN). Existing charging scheduling algorithms suffer from high node redundancy and energy consumption issues. In this paper, we study WSN charging problem from the perspectives of energy conservation combined with energy replenishment scheduling. Firstly, we detect the redundant nodes whose energy is wasted in the network functionality and develop a K‐covering redundant nodes sleeping scheduling algorithm (KRSS) for reducing energy. Secondly, we employed multiple wireless charging vehicles (WCVs) for energy replenishment and optimize the charging scheduling algorithm to prevent any exhaustion of nodes, and we proposed a distance and energy–oriented charging scheduling algorithm (DECS) with multiple WCVs. Simulation experiments are conducted to show the advantages of the proposed KRSS+DECS, confirming that our scheme is capable of removing redundant nodes, lowering node failures, and prolonging network lifetime. We detect the redundant nodes and develop a K‐covering redundant nodes sleeping scheduling algorithm for reducing energy. We employed multiple wireless charging vehicles for energy replenishment and optimize the charging scheduling to prevent any exhaustion of nodes. We proposed a distance and energy–oriented charging scheduling algorithm with multiple WCVs.